**Question 1: **Solve the given equation by using substitution method.

2x+3y=6, 4x+y=9

** Solution: **

The given equations are,

2x+3y=6................(1)

4x+y=9..................(2)

Arranging the second equation we get,

y=9-4x

Substitute this in equation (1) and simplify it.

So, 2x+3(9-4x)=6

2x+27-12x=6

-10x=6-27=-21

x=$\frac{21}{10}$=2.1

Put this value in (1)

2×2.1+3y=6

3y=6-4.2=1.8

y=$\frac{1.8}{3}$=0.6

The solution is (x,y)=(2.1,0.6)

**Question 2: **Solve the given equation using substitution method.

4x+8y=11 and 6x+2y=8

** Solution: **

The given equations are,

4x+8y=11................(1)

6x+2y=8..................(2)

Arranging the second equation we get,

2y=8-6x

y=$\frac{8-6x}{2}$

y=4-3x

Substitute this in equation (1) and simplify it.

So, 4x+8(4-3x)=11

4x+32-24x=11

-20x=11-32=-21

x=$\frac{21}{20}$=1.05

Put this value in (1)

4×1.05+8y=11

8y=11-4.2=6.8

y=$\frac{6.8}{8}$=0.85

The solution is (x,y)=(1.05,0.85)